How Do We Experience Digital Arts? An Exploration through Latour’s Modes of Existence - Schlienger, Dominik (MIT Press, 2023)
According to Bruno Latour the technical, despite being everything, is mostly experienced through its failure. If we take him by his word, what is it then that we experience when we speak of “digital art”? How does this bear on conceptualizations of technologies? In addition to the technical, the fictional mode and the mode of reference help to understand the notion of the digital as it pervades culture and media. Using examples from music, visual arts and an experimental artistic practice dystopian visions of technology are disentangled, re-configured. Embodied agency and kinaesthesia play a major role in this process.
Keywords: teknologia; musiikki; digitaalitekniikka; filosofia